2022
DOI: 10.3390/cells11071237
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Endocannabinoid Signalling in AD

Abstract: Chronic inflammation in Alzheimer’s disease (AD) has been recently identified as a major contributor to disease pathogenesis. Once activated, microglial cells, which are brain-resident immune cells, exert several key actions, including phagocytosis, chemotaxis, and the release of pro- or anti-inflammatory mediators, which could have opposite effects on brain homeostasis, depending on the stage of disease and the particular phenotype of microglial cells. The endocannabinoids (eCBs) are pleiotropic bioactive lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 162 publications
(229 reference statements)
0
17
0
Order By: Relevance
“…are also involved in crosstalk between microglia and neurons, as microglia also secretes such factors and both neurons and microglia express their receptors ( Szepesi et al, 2018 ). Accumulating evidence indicates that the microglial endocannabinoid system functions as a “non-canonical” signaling mechanism in the management of neuron–microglia crosstalk, thereby assisting microglia in regulating brain inflammation ( Castillo et al, 2012 ; Scipioni et al, 2022 ). CB1Rs are predominantly expressed in neurons, whereas CB2Rs are characteristic of microglia, especially during neuroinflammation ( Komorowska-Müller and Schmöle, 2021 ).…”
Section: Microglia and Its Interaction With Brain Cellsmentioning
confidence: 99%
“…are also involved in crosstalk between microglia and neurons, as microglia also secretes such factors and both neurons and microglia express their receptors ( Szepesi et al, 2018 ). Accumulating evidence indicates that the microglial endocannabinoid system functions as a “non-canonical” signaling mechanism in the management of neuron–microglia crosstalk, thereby assisting microglia in regulating brain inflammation ( Castillo et al, 2012 ; Scipioni et al, 2022 ). CB1Rs are predominantly expressed in neurons, whereas CB2Rs are characteristic of microglia, especially during neuroinflammation ( Komorowska-Müller and Schmöle, 2021 ).…”
Section: Microglia and Its Interaction With Brain Cellsmentioning
confidence: 99%
“…This literature review presents the first systematic analysis of pre-clinical data on the modulation of glial cells by cannabinoids that affects cognitive performance. Evidence of the impact of glial cell endocannabinoid signaling on cognitive deficits in AD was demonstrated by the attenuation of memory impairment ( Dominicis et al, 2022 ). The summary of the glial cell endocannabinoid mechanisms in cognition extracted from each article is presented in Supplementary Table S2 .…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids elicit CB2R activation in microglia, which is responsible for their immunological effects. For example, CB2R activation inhibits the release of pro-inflammatory mediators, including TNF- α and free radicals, while promoting microglial cell proliferation and migration ( Carrier et al, 2004 ; Dominicis et al, 2022 ). Therefore, activating CB2R in microglia might favorably affect inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was demonstrated that endocannabinoids or synthetic and natural cannabinoid compounds promote an anti-inflammatory activity in central and peripheral macrophages [ 152 , 192 , 193 ], disclosing a complex immunomodulation by these pleiotropic bioactive lipid messengers.…”
Section: The Role Of Endocannabinoids In Low-grade Inflammation and M...mentioning
confidence: 99%